The features of a deauthentication attack implementation in networks 802.11 - Корольков, Роман Юрійович; Куцак, Сергій Вікторович (Ukrainian Information Security Research Journal, 2019)
The special type of attack – Denial of Service (DoS) in networks based on the 802.11 standard, namely the deauthentication attack, was investigated and demonstrated in the article. This study illustrates the possible scheme of action of the attacker and the scenario of attack on the client. The possibility of a deauthentication attack implementing is directly related to the features of the mechanism of communication in a wireless network 802.11. The connection between the client and the access point (AP) is established by exchanging different frames to undergo authentication and association procedures. Sending a deauthentication frame to Wi-Fi is a vulnerable point in the process of connecting (disconnecting) devices. Deauthentication frame is a notification, not a request. When receiving a deauthentication frame (regardless of whether it is fake or real), no host can refuse to execute it unless the frame protection mode (802.11w: MFP or Management Frame Protection) is enabled and failed to successfully complete control against counterfeiting frame of MIC (Message Integrity Check). Because authentication cancellation requests cannot be ignored, the access point reacts instantly to those requests. The attacker falsifies the MAC address of the legitimate client and runs periodic deauthentication frames. The AP responds by sending a customer authentication denial response. Such a vulnerability of wireless networks Wi-Fi, allows an attacker to send packets deauthentication, leading to disruption of communication between clients and access points to which they are connected. Should the attack continue indefinitely, the client will definitely not be able to connect to the wireless network until the attacker cancels the attack. Therefore, DoS attack is critical attack that violates the current load and transaction performed by the customer. Implementation of this type of attack is carried out using several tools in the Kali Linux 2016.2 operating system